2007
DOI: 10.1177/030802260707000905
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Leisure Occupations of Older Adults

Abstract: Participating in leisure is known to enhance physical wellbeing, mental health and social functioning. There is, however, little knowledge of the current level of engagement in leisure occupations by older adults in the United Kingdom. Therefore, the aim of this study was to explore the current leisure occupations of adults over 60 years who considered themselves to be healthy and to identify the motivations that underpinned participation in those occupations.Structured interviews were conducted with 70 adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 22 publications
2
38
0
1
Order By: Relevance
“…In this study, respondents attributed a number of psychological benefits to the knitting process, coming from its rhythmic and repetitive nature, which induced feelings of calm and relaxation. This echoes the findings from other studies, especially those related to leisure or arts and crafts (Ball et at 2007, Riley 2008. For the majority of respondents in this study, knitting was perceived as a means of unwinding from the stresses of everyday life or as a coping strategy for those with anxiety problems, pain or depression.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, respondents attributed a number of psychological benefits to the knitting process, coming from its rhythmic and repetitive nature, which induced feelings of calm and relaxation. This echoes the findings from other studies, especially those related to leisure or arts and crafts (Ball et at 2007, Riley 2008. For the majority of respondents in this study, knitting was perceived as a means of unwinding from the stresses of everyday life or as a coping strategy for those with anxiety problems, pain or depression.…”
Section: Discussionsupporting
confidence: 87%
“…Although social interaction may be synonymous with positive benefits (Taylor 2003, Ball et al 2007, this research found that aiming beyond the participant's physical capabilities had a negative impact on his or her self-esteem and confidence. If the physical demands are more than the capabilities of the person, the occupation may be stopped.…”
Section: Policy Implicationsmentioning
confidence: 67%
“…This leads us to conjecture that careful consideration of individual differences and design of customized instructional and support programs are more likely to positively impact the well-being of older adults, perhaps through the use of computerized educational modules and applications that promote healthy daily activity involvement. For example, toward this end the Internet could be used by older adults to obtain self-care oriented health information (El-Attar, Gray, Nair, Ownby, & Czaja, 2005), access information pertaining to local public transportation or leisure activities (Morell, Mayhorn, & Bennett, 2000), maintain health-promoting relationships with friend or family through email communications, or stay mentally active (Ball, Corr, Knight, & Lowis, 2007). …”
Section: Discussionmentioning
confidence: 99%